The Sesquiterpenoids from Aglaia cucullata Peel Fruit and Their Cytotoxic Activities Against B16-F10 and HeLa Cancer Cell Lines - Supratman, Unang; Anjari, Intan Hawina; Harneti, Desi; Naini, Al Arofatus; Farabi, Kindi; Anwar, Risyandi (Molekul, 2023)
Sesquiterpenoids are terpenoid derivative compounds that have a diverse chemical structure and pharmacological effects. Sesquiterpenoids can be found in many plants of Aglaia which is the large source of natural compounds in the Meliaceae family. This research was aimed to elucidate the structure of sesquiterpenoids from the peel fruit of Aglaia cucullata and their cytotoxic activities against two human cancer cell lines. The n-hexane extract was separated and further purified by various chromatographic methods to yiled three sesquiterpenoids. The structure of these sesquiterpenoids were identified by spectroscopy analysis including MS, IR, 1H-NMR, 13C-NMR and DEPT as well as compared with spectral data which reported previously. The sesquiterpenoid compounds 1-3 were identified as spathulenol (1), alismol (2), and 10-oxo-isodauc-3-en-15-al (3). The cytotoxic activity of three sesquiterpenoid compounds were tested against HeLa cervical cancer cell and B16-F10 skin cancer cell using the PrestoBlue method. Compound 2 exhibited the highest activity against both HeLa and B16-F10 cancer cell lines with IC50 48.11 μg/mL and 57.05 μg/mL, respectively.